A publicação da obra literária de José de Almada Negreiros - breves considerações - Silva, Celina (2012)
The present article studies the different versions of the several publications of Almada Negreiros literary works - Estampa (1970-1972), Imprensa-Nacional Casa da Moeda (1985-1993), Nova Aguilar (1997), Assírio & Alvim (2000-2005). In spite of the large gap between these publications and the difference of the publishing houses, they all present a common absence of quality. As a matter of fact they show a great number of errors from different nature such as the huge difference in what concerns the extension of the corpus, and the criteria of editing, never clarified in a precise way, the incoherent manner in which the several (never in the same number) volumes are organized, the lack of scientifically approach in text selection and in the organization. Until now the real dimension in a quantitative point of view remains unknown because this situation changes constantly from one edition to another. On the other hand it's surprising that in what concerns some of the text that had been published in different versions during the author life this fact isn't always respected. So the mentioned publications present some methodological weaknesses concerning the documental treatment. According to these data and considering the relevance of this works, the urgent need of a critical edition becomes a priority in order to establish a rigorous edition of this almost unknown author.